Optimized formulation of solid self-microemulsifying sirolimus delivery systems - Cho W (Dove Medical Press, 2013)
Wonkyung Cho,1,2 Min-Soo Kim,3 Jeong-Soo Kim,2 Junsung Park,1,2 Hee Jun Park,1,2 Kwang-Ho Cha,1,2 Jeong-Sook Park,2 Sung-Joo Hwang1,4 1Yonsei Institute of Pharmaceutical Sciences, Yonsei University, Incheon, Republic of Korea; 2College of Pharmacy, Chungnam National University, Daejeon, Republic of Korea; 3Department of Pharmaceutical Engineering, Inje University, Gimhae, Republic of Korea; 4College of Pharmacy, Yonsei University, Incheon, Republic of Korea Background: The aim of this study was to develop an optimized solid self-microemulsifying drug delivery system (SMEDDS) formulation for sirolimus to enhance its solubility, stability, and bioavailability. Methods: Excipients used for enhancing the solubility and stability of sirolimus were screened. A phase-separation test, visual observation for emulsifying efficiency, and droplet size analysis were performed. Ternary phase diagrams were constructed to optimize the liquid SMEDDS formulation. The selected liquid SMEDDS formulations were prepared into solid form. The dissolution profiles and pharmacokinetic profiles in rats were analyzed. Results: In the results of the oil and cosolvent screening studies, Capryol™ Propylene glycol monocaprylate (PGMC) and glycofurol exhibited the highest solubility of all oils and cosolvents, respectively. In the surfactant screening test, D-α-tocopheryl polyethylene glycol 1000 succinate (vitamin E TPGS) was determined to be the most effective stabilizer of sirolimus in pH 1.2 simulated gastric fluids. The optimal formulation determined by the construction of ternary phase diagrams was the T32 (Capryol™ PGMC:glycofurol:vitamin E TPGS = 30:30:40 weight ratio) formulation with a mean droplet size of 108.2 ± 11.4 nm. The solid SMEDDS formulations were prepared with Sucroester 15 and mannitol. The droplet size of the reconstituted solid SMEDDS showed no significant difference compared with the liquid SMEDDS. In the dissolution study, the release amounts of sirolimus from the SMEDDS formulation were significantly higher than the raw sirolimus powder. In addition, the solid SMEDDS formulation was in a more stable state than liquid SMEDDS in pH 1.2 simulated gastric fluids. The results of the pharmacokinetic study indicate that the SMEDDS formulation shows significantly greater bioavailability than the raw sirolimus powder or commercial product (Rapamune® oral solution). Conclusion: The results of this study suggest the potential use of a solid SMEDDS formulation for the delivery of poorly water-soluble drugs, such as sirolimus, through oral administration. Keywords: sirolimus, solubility, stability, bioavailability, self-emulsifying drug delivery systems, microemulsion